Family Educational Practices in the development of social skills rumble between two five year old and in the city of Medellin (Encuentros, 2017)
Article derivative aimed at analyzing the relationships present family educational practices and performance in social skills of children between 2 and 5 years old in the city of Medellín research. The actions of the parents were evaluated from educational practices family: authoritarian, permissive balanced and the Family Educational Practices Scale (PEF) Alonso and Román (2003) and played by six social behavioral repertoires studied by Monjas (2000). The research was descriptive correlational. It worked with a sample of 100 children and their families. The results show respect to family educational practices that increased use of authoritarian and permissive strategies by less developed families of codes to interact with other people present children, in contrast to more balanced presence of further development practices repertoires to interact with other.